Seasonality of cardiovascular risk factors: an analysis including over 230 000 participants in 15 countries. Issue 19 (30th May 2014) - Marti-Soler, Helena; Gubelmann, Cédric; Aeschbacher, Stefanie; Alves, Luis; Bobak, Martin; Bongard, Vanina; Clays, Els; de Gaetano, Giovanni; Di Castelnuovo, Augusto; Elosua, Roberto; Ferrieres, Jean; Guessous, Idris; et al.
Abstract : Objective: To assess the seasonality of cardiovascular risk factors (CVRF) in a large set of population-based studies. Methods: Cross-sectional data from 24 population-based studies from 15 countries, with a total sample size of 237 979 subjects. CVRFs included Body Mass Index (BMI) and waist circumference; systolic (SBP) and diastolic (DBP) blood pressure; total, high (HDL) and low (LDL) density lipoprotein cholesterol; triglycerides and glucose levels. Within each study, all data were adjusted for age, gender and current smoking. For blood pressure, lipids and glucose levels, further adjustments on BMI and drug treatment were performed. Results: In the Northern and Southern Hemispheres, CVRFs levels tended to be higher in winter and lower in summer months. These patterns were observed for most studies. In the Northern Hemisphere, the estimated seasonal variations were 0.26 kg/m 2 for BMI, 0.6 cm for waist circumference, 2.9 mm Hg for SBP, 1.4 mm Hg for DBP, 0.02 mmol/L for triglycerides, 0.10 mmol/L for total cholesterol, 0.01 mmol/L for HDL cholesterol, 0.11 mmol/L for LDL cholesterol, and 0.07 mmol/L for glycaemia. Similar results were obtained when the analysis was restricted to studies collecting fasting blood samples. Similar seasonal variations were found for most CVRFs in the Southern Hemisphere, with the exception of waist circumference, HDL, and LDL cholesterol. Conclusions: CVRFs show a seasonal pattern characterised by higher levels in winter, and lower levels in summer. This pattern could contribute to the seasonality of CV mortality.